Acute severe hepatitis with alemtuzumab and rechallenge after a year. (February 2019) - Beattie, William; Yan, Bernard; Sood, Siddharth
Highlights: Alemtuzumab is used for the treatment of relapsing remitting multiple sclerosis. Other monoclonal antibodies are known to cause drug induced liver injury. This case is the first description of drug induced liver injury due to alemtuzumab. Liver function tests should be monitored during alemtuzumab treatment. Abstract: Alemtuzumab is a monoclonal antibody used as a disease modifying agent in relapsing and remitting multiple sclerosis. It has not previously been associated with drug induced liver injury. Here we present a case of a 49 year old female developing drug induced liver injury secondary to alemtuzumab, confirmed upon rechallenge. Our patient developed severe hepatitis within two days of starting alemtuzumab, both initially and upon rechallenge. The alanine aminotransferase peaked at 577 units per litre and 426 units per litre after initial dose of alemtuzumab and rechallenge respectively. The patient's liver function tests improved significantly between doses of alemtuzumab and again normalised within three months of the second dose, with no clinical manifestations of acute hepatic failure. A full hepatitis screen ruled out alternative causes of hepatitis, including autoimmune hepatitis and hepatotoxicity relating to other medications. Deliberate rechallenge with a medication thought to be associated with drug induced liver injury is uncommonly performed but provides substantial evidence for causality in the appropriate clinical context. The Roussel Uclaf Causality Assessment Method score was calculated as nine, indicating that drug induced liver injury due to alemtuzumab is highly probable. Drug induced liver injury is a potentially serious condition that should be monitored for during alemtuzumab treatment of relapsing and remitting multiple sclerosis. The role of a rechallenge should be weighed up on a case by case basis.